Trigger points: enhancing generic skills in accounting education through changes to teaching practices - T. Watts; C. J. McNair (Australasian Accounting, Business and Finance Journal, 2008)
In 2001 a small Australian university implemented particular intervention strategies designed to improve specific educational outcomes in its accounting degree program. These outcomes mirrored the three core areas of the Graduate Careers Council of Australia’s Course Experience Questionnaire: (1) good teaching, (2) overall satisfaction, and (3) generic skills. Five areas were identified for intervention: (1) the effective allocation of full-time staff, (2) the effective use of sessional staff, (3) greater commitment by sessional staff, (4) the introduction of common subject outlines, and (5) the proactive response to student evaluations. The results indicate a statistically significant improvement in 2003 in the three core areas, supporting the argument that improving student satisfaction with their educational experience will improve student outcomes. A similar, but less significant, improvement of grades in the three final year accounting subjects was identified. Suggestions for the decline from 2004 are also explored.
Keywords: Accounting education; student performance; student satisfaction; Intervention